2012
DOI: 10.1590/s0100-204x2012001100001
|View full text |Cite
|
Sign up to set email alerts
|

Produção e acúmulo de nutrientes em povoamento de eucalipto em consequência da intensidade do desbaste e da fertilização

Abstract: Resumo -O objetivo deste trabalho foi estimar a produção de madeira e biomassa, bem como a quantidade de nutrientes acumulada, em povoamento de eucalipto submetido a intensidades de desbaste e à fertilização pós-desbaste. O experimento foi realizado em blocos ao acaso, em parcelas subdividas, com duas repetições dos tratamentos dentro de cada bloco. Nas parcelas, foram avaliadas quatro intensidades de desbaste (0, 20, 35 e 50%) e, nas subparcelas, as condições com e sem fertilização pós-desbaste. O desbaste fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
0
12
0
4
Order By: Relevance
“…Eucalyptus production with a cultivation cycle of 7 years accumulates between 23 and 38 kg¨ha´1 of P [40][41][42][43]. Thus, in all sites there is potential supply for a high demand of P (50 kg¨ha´1) in Eucalyptus plantations [44,45]. This indicates the need to improve routine analysis methods for the quantification of available P in soil.…”
Section: Distribution Of Organic and Inorganic P Fractionsmentioning
confidence: 99%
“…Eucalyptus production with a cultivation cycle of 7 years accumulates between 23 and 38 kg¨ha´1 of P [40][41][42][43]. Thus, in all sites there is potential supply for a high demand of P (50 kg¨ha´1) in Eucalyptus plantations [44,45]. This indicates the need to improve routine analysis methods for the quantification of available P in soil.…”
Section: Distribution Of Organic and Inorganic P Fractionsmentioning
confidence: 99%
“…Silva et al (2012) observed an increase of 14.2% in diameter 36 months after a 50% reduction in basal area in 89 months old eucalypt plantation. Pinus taeda thinned at the age of 132 months presented an increase of 37.4% in diameter 72 months after thinning (ELESBÃO; SCHNEIDER, 2011).…”
Section: Discussionmentioning
confidence: 82%
“…As the population becomes older, high density planting accentuates the growth resource limitations which favor the mortality of dominated individuals. The death of trees is slow at first and then becomes faster and more intense, which explains natural selection, where individuals that are more vigorous and better adapted to the environment keep growing, with greater chances of survival (SMITH et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This practice is an important strategy for the resumption of growth of forest stands, concentrating the production potential in an ever smaller number of individuals (Silva et al, 2012). Thinning is also important to increase the transmittance of photosynthetically active radiation for higher forage production in AFSs .…”
Section: Technical Thinning Age (Tta)mentioning
confidence: 99%